CONTINUOUS IMPROVEMENT IN SCHOOL ADMINISTRATION: PARTICIPATORY MANAGEMENT AS A PATH TO QUALITY IN THE SECRETARIAT OF A PUBLIC SCHOOL IN THE MUNICIPALITY OF EIRUNEPÉ-AM - de Souza, Maria Lins França; Chavier, Francisca das Chagas Estevão; Cavalcanti, Patrícia Maria Moreira; Maganhães, Cilene Farias Batista; Belém, Romário Rodrigues; Reis, Gustavo Costa; Vasconcelos, Raimundo da Silva; Fialho, Rayla da Silva (Seven Editora, 2025)
This article analyzes how participatory management can contribute to the continuous improvement of school administration, focusing on the secretariat of a public School located in Eirunepé, Amazonas. The main objective is to understand the impacts of active community involvement in administrative processes, identifying challenges and proposing strategies to strengthen more democratic and effective management practices. The study adopts a mixed- methods approach, with a qualitative emphasis, and employs structured questionnaires as the primary data collection instrument, targeting school stakeholders such as administrators, teachers, students, staff, and parents or guardians. The results reveal that, despite limitations such as centralized decision-making and low family engagement, there is significant potential for strengthening a participatory culture, especially when active listening, dialogue, and shared responsibility are encouraged. The study concludes that participatory management, when combined with simple yet intentional practices within the school secretary’s office, can foster a more welcoming, efficient environment that meets the real needs of the educational community, reaffirming the public school’s commitment to quality and citizenship. DOI: https://doi.org/10.56238/sevened2025.026-031